P251 The Role of Reactive Oxidative Species Within Cigarette Smoke Extract on Apoptosis and Inflammation in Primary Nasal Epithelial Cells. (19th November 2012) - Comer, D; Elborn, JS; Ennis, M
Abstract : Introduction: The responses of the bronchial epithelium to cigarette smoke (CS) are well characterized, but effects on the nasal epithelium, also important in respiratory disease, are not as well defined. The mechanism of cell death due to cigarette smoke extract (CSE) exposure is controversial. As there is convincing evidence that cigarette smoke decreases levels of protective antioxidants, we hypothesised that reactive oxidative species contained within CSE contribute to its immunomodulatory and cytotoxic properties. Methods: Nasal brushings were obtained from 16 healthy volunteers from the medial aspect of the inferior turbinate as previously described. CSE was prepared by combusting 1 Marlboro cigarette through 25 ml of media. Cell viability was determined after primary nasal epithelial cells (PNECs) were stimulated with 5% CSE for 24 h (caspase 3 levels determined after 4 h), in the presence or absence of 20 mM N-acetylcysteine (NAC). In separate experiments, cultures were stimulated with Pseudomonas aeruginosa lipopolysaccharide (PA LPS) for 24 h (0 – 30 µg/ml), and the effects of pre-incubation with CSE±20 mM NAC for 4 h evaluated in terms of cytokine release. Phospho-NF-κB activity was determined after 1 h PA LPS exposure. Apoptosis was evaluated using annexin-V staining and the terminal transferase-mediated dUTP nick end-labelling (TUNEL) method. Results: 5% CSE (4 h) exposure was immunosuppressive in PNEC cultures for both IL-8 and IL-6 release (0.53 fold reduction in IL-8 and 0.49 fold reduction in IL-6 release after stimulation with 30 µg/ml PA LPS for 24 h). 4 h exposure to CSE heightened active caspase 3 levels, and a 24 h exposure induced both early and late apoptosis established by annexin-V staining (Table 1 ). Apoptosis was confirmed using the TUNEL assay. All of these effects were mitigated with the addition of 20 mM NAC to the CSE (0.85 fold reduction in IL-8 and 0.73 fold reduction in IL-6 release after stimulation with 30µg/ml PA LPS for 24 h). Conclusions: A 4 h CSE exposure was immunosuppressive in PNEC cultures and induced apoptosis. Reactive oxidative species are at least partially responsible for these observations. Research funded by NI RDO.